1998
DOI: 10.1200/jco.1998.16.2.754
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-dose oral granisetron versus intravenous ondansetron in the prevention of nausea and vomiting induced by moderately emetogenic chemotherapy: a multicenter, double-blind, randomized parallel study.

Abstract: A single oral dose of granisetron (2 mg) resulted in equivalent levels of antiemetic protection as I.V. ondansetron (32 mg). Both agents were well tolerated, although more dizziness and abnormal vision were reported with ondansetron. Because the two antiemetic regimens exhibited equivalent efficacies, additional factors such as convenience and cost of therapy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 14 publications
3
68
1
Order By: Relevance
“…But in case of delayed emesis the antiemetic protection had achieved 43.3% in children receiving ondansetron and on the contrary, 80% in children treated with granisetron who had achieved complete response and their observation was very much statistically significant 1 .Our observation had also matched with the study done by Friedman et al, where they had showed that at 48 hours of treatment, granisetron group of children had achieved A separate study was done by Perez et al, where they compared the single oral dose of granisetron versus IV ondansetron to prevent CRNV by moderate emetogenic chemotherapeutic agents and they observed no significant emetogenic control during 24 hours of chemotherapy 23 ,which are against our observations, where it was found that ondansetron group of children achieved 60% complete response at 48 hours, on the other hand, granisetron group had achieved 93.3% complete response following chemotherapy and the findings were statistically significant.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…But in case of delayed emesis the antiemetic protection had achieved 43.3% in children receiving ondansetron and on the contrary, 80% in children treated with granisetron who had achieved complete response and their observation was very much statistically significant 1 .Our observation had also matched with the study done by Friedman et al, where they had showed that at 48 hours of treatment, granisetron group of children had achieved A separate study was done by Perez et al, where they compared the single oral dose of granisetron versus IV ondansetron to prevent CRNV by moderate emetogenic chemotherapeutic agents and they observed no significant emetogenic control during 24 hours of chemotherapy 23 ,which are against our observations, where it was found that ondansetron group of children achieved 60% complete response at 48 hours, on the other hand, granisetron group had achieved 93.3% complete response following chemotherapy and the findings were statistically significant.…”
Section: Discussionsupporting
confidence: 70%
“…Confident interval (CI) was 95% and their subjective assessment had revealed no difference. The investigators had concluded that single 24 mg oral ondansetron is safe and effective compared to single IV infusion of 10ìgm/kg of granisetron in the prevention of nausea vomiting in high emetogenic chemotherapy 11 , which is in contrast to study done by Perez 23 . But our findings had proved that granisetron is more effective than ondansetron in the prevention of both acute (90% vs 70%) and delayed onset (80% vs 43.4%) nausea and emesis.…”
Section: Discussioncontrasting
confidence: 52%
“…In directly comparative, single-agent studies of 5-HT 3 -receptor antagonists that permitted concomitant corticosteroid use [39,52], the addition of the steroid improved total control rates by 9.8%-13.4% at 24 hours and by 4.7%-8.7% at 48 hours postchemotherapy. Results from a study investigating optimum corticosteroid doses suggest that a dexamethasone dose of 20 mg be used as standard prophylaxis in combination with 5-HT 3 -receptor antagonists [72] ( Table 3).…”
Section: Potential For Corticosteroid Combinationmentioning
confidence: 99%
“…5-HT 3 -receptor antagonists have become the agents of choice in preventing acute CINV following both moderately and highly emetogenic chemotherapy [11,51]. Complete response and total control rates seen with specific drugs range from 60%-80% for moderately emetogenic chemotherapy [4,[52][53][54], 40%-60% for cisplatin-containing therapy [4,33,55,56], and 25%-60% for high-dose cisplatin regimens [33,35,47,57,58].…”
Section: Optimizing Efficacymentioning
confidence: 99%
“…When the trial was initiated granisetron was available in Denmark for intravenous use only. It has now been shown that a single oral dose of 2 mg granisetron is as effective as intravenous treatment with a serotonin antagonist (Perez et al, 1998).…”
Section: Discussionmentioning
confidence: 99%